Automação do dimensionamento estrutural de fundações – sapatas e blocos - Alves, Antonio Domingos (Universidade Federal Rural do Semi-Árido, 2018)
The foundations are responsible for transmitting all the loads of the superstructure of a building to the ground, these can be classified as being shallow or deep. Shallow foundations are elements in which the load is transmitted to the ground, predominantly by the distributed pressure under the base of the Foundation. The deep foundations are elements that transmit the load to the ground by the base, by your side or by a combination of the two. This work is an applied research, where the author offers a solution for the design and detailing of structural shallow foundations. Has as its objective the development of a program able to size and detail shallow Foundation of type shoes and Foundation blocks, as well as calculating the permissible load capacity of the soil and the repression suffered by the same immediately. For this, you will use the Excel software. Initially searches were carried out in order to select and understand the main and most reliable methods of calculations used. From that, they were inserted coefficients and parameters needed for the calculations in spreadsheets. Subsequently, the automation of the calculations for the design of structural elements reliably. The results calculated by the program were compared to examples from literature and other structural calculation software, showing errors between 5 and 10%, thus, reliability and safety for users.
Keywords: Fundações; Capacidade de Carga; Recalque; ENGENHARIAS::ENGENHARIA CIVIL